KENYAMANAN BALE METEN RUMAH TRADISIONAL DITINJAU DARI SUDUT ERGONOMIS DI DESA ADAT BATUAN SUKAWATI GIANYAR BALI - Sudarmanto, I Gede; Mahayana, I Made Bulda; Jirna, I Nyoman (Jurnal Kesehatan Lingkungan (JKL), 2024)
Abstract. Residential houses have forms and functions to protect humans from natural influences. A good house must meet several requirements such as; environmental planning, spatial planning, building planning and utilities. Traditional Balinese architecture basically combines two main human needs, namely "scale-niskala" (both inner and outer), which is based on Hindu religious philosophy starting from spatial planning, forms, materials and structures. Problems with the original "Bale Meten" such as: dust, stuffiness, smell, humidity 59-63%, lighting 10-60 lux. Due to the times, "Bale Meten" automatically changes to a new function, namely for studying and sleeping, so that many people make modifications to their "Bale Meten". This research was conducted in the Batuan Traditional Village, Sukawati District, Gianyar Regency, Bali, in 2022, with the aim of finding out whether the original "Bale Meten" and modified "Bale Meten" meet ergonomic requirements or not. The sample consists of 60 "Bale Meten", with variables including: lighting, temperature, humidity, air circulation (micro climate). This type of research is "descriptive exploratory" with an "analytical cross-sectional" design. Data collection was carried out by way of interviews, observation, and measurement, while data analysis was in the form of "descriptive and analytic". The results obtained stated that the comfort of the original "Bale Meten" and the modified "Bale Meten" did not meet the ergonomic requirements. Microclimate affects comfort, while windows and ventilation affect microclimate. The solution is to socialize to the community how to build houses that meet technical and ergonomic requirements, so that they become healthy and livable homes.